THE SQUARED COMMUTATIVITY DEGREE OF DIHEDRAL GROUPS (Jurnal Teknologi (Sciences & Engineering), 2016)
The commutativity degree of a finite group is the probability that a random pair of elements in the group commute. Furthermore, the n-th power commutativity degree of a group is a generalization of the commutativity degree of a group which is defined as the probability that the n-th power of a random pair of elements in the group commute. In this paper, the n-th power commutativity degree for some dihedral groups is computed for the case n equal to 2, called the squared commutativity degree.